Variation in Diabetes Management: A National Assessment of Primary Care Providers. (January 2020) - Peabody, John W.; de Belen, Enrico; Dahlen, Jeffrey R.; Acelajado, Maria Czarina; Tran, Mary T.; Paculdo, David R.
Background: Glucose control is monitored primarily through ordering HbA1c levels, which is problematic in patients with glycemic variability. Herein, we report on the management of these patients by board-certified primary care providers (PCPs) in the United States. Methods: We measured provider practice in a representative sample of 156 PCPs. All providers cared for simulated patients with diabetes presenting with symptoms of glycemic variability. Provider responses were reviewed by trained clinicians against evidence-based care standards and accepted standard of care protocols. Results: Care varied widely—overall quality of care averaged 51.3%±10.6%—with providers performing just over half the evidence-based practices necessary for their cases. More worryingly, provider identified the underlying etiology of the poor glycemic control only 36.3% of the time. HbA1c was routinely ordered in 91.3% of all cases but often (59.5%) inappropriately. Ordering other tests of glycemic control (done in 15% of cases) led to significant increases in identifying the etiology of the hyperglycemia. Correctly modifying their patient's treatment was more likely to occur if doctors first identified the underlying etiology (65.9% vs 49.0%, P <0.001). We conservatively estimated a US $65/patient/visit in unnecessary testing and US $389 annually in additional care costs when the etiology was missed, translating potentially into millions of dollars of wasteful spending. Conclusion: Despite established evidence that HbA1c misses short-term changes in diabetes, we found PCPs consistently ordered HbA1c, rarely using other available blood tests. However, if the factors leading to poor glycemic control were recognized, PCPs were more likely to correctly alter their patient's hypoglycemic therapy.